The outcome of eosinophilic granuloma involving unilateral atlantoaxial joint: A case report and literature review. Issue 25 (June 2017) - Song, Yu; Geng, Wen; Guo, Tao; Gao, Yong; Zhang, Yukun; Li, Shuai; Wang, Kun; Tu, Ji; Yang, Cao
Abstract: Rationale: Solitary eosinophilic granuloma (EG), the most benign, common form of Langerhans cell histiocytosis, has a self-limiting process and is associated with a good prognosis. Immobilization is recommended as the first treatment strategy for solitary EG, although the treatment protocols are still controversial. Radiotherapy and surgery are secondary treatment choices. Lesions of the upper cervical spine react differently to treatment because of their specific anatomical and motor features. Patient concerns: We discuss the case of a 29-year-old man with axis EG who underwent immobilization, radiotherapy, and finally surgery. Diagnosis: Eosinophilic granuloma (EG). Interventions: An initial conservative protocol, including immobilization with a collar and radiotherapy, effectively relieved his neck pain, whereas torticollis secondary to atlantoaxial subluxation was not improved. Therefore, he underwent tumor resection through the anterior approach and spinal reconstruction, fixation, and fusion through the posterior approach. Outcomes: The deformity was well corrected and follow-up was satisfactory. Lessons: Upon review of the literature, we found that EG lesions affecting the axis have more risk factors for instability or deformity, and they have particular anatomical and motor characteristics; thus, they require more consideration and attention in terms of treatment, prognosis, and follow-up.